2015
DOI: 10.1016/j.rmo.2016.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de carga bacteriana en brackets metálicos versus brackets cerámicos

Abstract: Objective: To assess the bacterial load in metallic and ceramic brackets and determine which favor dental plaque retention. Material and methods: Extracted premolars divided into 2 groups and analyzed. In one group metal brackets were placed and in the other group, ceramic brackets. Results: Statistical analysis were performed and it was determined that there was no significant difference. Conclusion: The type of bracket used in the orthodontic treatment, is not a determining factor in bacteria adhesion and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
2
0
3
Order By: Relevance
“…The results of the inhibition halos produced with each concentration of AgNPs, showed that in the qualitative evaluation of sensitivity it is evident that 100% of the samples at 25 ppm have activity | null on Mutans streptococci; at 75 ppm 50% (10; 20) Tristán et al 7 , en su estudio "Future impact of nanotechnology on medicine and dentistry" manifiestan que cada vez existen más aplicaciones concretas como la de las nanopartículas de plata en la medicina y la odontología, se utilizan como una alternativa más segura para empastes dentales ya que poseen propiedades antidesgaste, antifúngicas y antibacterianas. Para Cardoso 8 existe un número creciente de informes sobre la actividad bactericida de Ag-NPs y sobre su actividad contra biofilms bacterianos.…”
Section: Resultsunclassified
See 4 more Smart Citations
“…The results of the inhibition halos produced with each concentration of AgNPs, showed that in the qualitative evaluation of sensitivity it is evident that 100% of the samples at 25 ppm have activity | null on Mutans streptococci; at 75 ppm 50% (10; 20) Tristán et al 7 , en su estudio "Future impact of nanotechnology on medicine and dentistry" manifiestan que cada vez existen más aplicaciones concretas como la de las nanopartículas de plata en la medicina y la odontología, se utilizan como una alternativa más segura para empastes dentales ya que poseen propiedades antidesgaste, antifúngicas y antibacterianas. Para Cardoso 8 existe un número creciente de informes sobre la actividad bactericida de Ag-NPs y sobre su actividad contra biofilms bacterianos.…”
Section: Resultsunclassified
“…Tristan and colls. 7 , in their study "Future impact of nanotechnology on medicine and dentistry", they state that there are more and more specific applications such as silver nanoparticles in medicine and dentistry, they are used as a safer alternative for dental fillings as they have antiwear, antifungal and antibacterial properties. For Cardoso 8 there is an increasing number of reports on the bactericidal activity of Ag-NPs and on their activity against bacterial bio-films.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations